Factor Analysis of Working Mothers and Housewives of Preschool Children 36-72 Month in Kindegarten Againt Stunting in the Kalisari District, Mulyorejo District, Surabaya - Setiana Andarwulan; Annah Hubaedah; Yuni Khoirul Waroh (Proceeding of International Conference on Science, Health, And Technology, 2019)
Every family expects their children to grow and develop optimally (physically, mentally or cognitively and socially healthy), to be proud of, and to be useful for their homeland and nation. The level of achievement of a person's biological potential is the result of interactions between genetic factors and the bio-physio-psychosocial environment (biological, physical and psychosocial). The problem of malnutrition that has received much attention lately is the problem of chronic nutrition in the form of short children (stunting). Stunting is a chronic nutritional problem, meaning that it arises as a result of a state of malnutrition that accumulates over a long period. Nurturing and busy work is a factor that is very closely related to the growth and development of children under five years old. The study design was conducted in the form of quantitative research, by taking the population of kindergarten children in the city of Surabaya with a sampling technique in the form of probability sampling. Sampling was carried out randomly and it was decided that kindergarten in Kalisari village would be a sample of 64 children. The results showed that the Chi-Square value of 0.409 was smaller than the value of α = 0.5. So that shows a weak scale analysis. This means that working mothers do not have whole kindergarten-aged children with stunting.